If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 81 + -1(9 + -2x)(9 + -2x) Multiply (9 + -2x) * (9 + -2x) y = 81 + -1(9(9 + -2x) + -2x * (9 + -2x)) y = 81 + -1((9 * 9 + -2x * 9) + -2x * (9 + -2x)) y = 81 + -1((81 + -18x) + -2x * (9 + -2x)) y = 81 + -1(81 + -18x + (9 * -2x + -2x * -2x)) y = 81 + -1(81 + -18x + (-18x + 4x2)) Combine like terms: -18x + -18x = -36x y = 81 + -1(81 + -36x + 4x2) y = 81 + (81 * -1 + -36x * -1 + 4x2 * -1) y = 81 + (-81 + 36x + -4x2) Combine like terms: 81 + -81 = 0 y = 0 + 36x + -4x2 y = 36x + -4x2 Solving y = 36x + -4x2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 36x + -4x2
| 2x-3=2(x-6) | | 1.8x=4.8 | | 3x-21+1=x | | 0.12(y-3)+0.14y=0.06y-0.01(70) | | 4x+2=x | | 5p=6+4p | | 4z+0.375=5z+0.125 | | 4x-10y-1z=-51 | | 9-4(4-(7y-6))= | | -6x-20y+1z=-63 | | z^7+9z^6=0 | | (x+(2-i))(x-(2-i))=0 | | 0.20x+0.45(50)=29.5 | | 9(2y-6)-(5y+3)= | | 6r^7+6r^5=0r^6+9r^4 | | (20-2x)*(40-2x)*x=x | | (v+3)(v-4)=v | | (4x+16)= | | 3(2k+4)-13k+4+2= | | 4.8x-8.4y-4.5=0 | | 0.007(x+3)=0.008x+0.0018 | | -3k+5k-5+2k= | | -.1x+2.1y=-9.7 | | 17y-73=y-4 | | 13r+s+20r+11s= | | 0.9z=13z | | -2(x-7)+7=21 | | (0)b=1 | | 17(y-73)=y-4 | | y=x^3+x^2-16x-16 | | 50x-60= | | -8+7y=-56 |